The extraction and determination of ellagic acid and resveratrol in blueberry species by HPLC-DAD and LCMS/MS - AYAZ SEYHAN, SERAP (My University, 2023)
© 2023 Marmara University Press.Ellagic acid (EA) and resveratrol (RES) are phenolic compounds naturally found in fruits. However, a significant amount of RES and EA is present in berries and their effective isolation enables the production of functional foods. In this study, EA and RES found in four highbush (Vaccinium corymbosum) blueberry varieties (Bluecrop, Brigitta, Darrow and Bluejay) were analyzed simultaneously for the first time. A chromatographic method was developed for EA and RES by HPLC-DAD and LC-MS/MS. Furthermore, pressurized liquid extraction (PLE) method was performed for the extraction of EA and RES from blueberry samples. LOD (limit of detection) and LOQ (limit of quantification) were determined as 0.1898x10-6 mol.L-1 and 0.5694x10-6 mol.L-1 for RES, 0.1271x10-6 mol.L-1 and 0.3814x10-6 mol.L-1 for EA, respectively. All the results were reevaluated according to 91.85% and 84.97% recovery value, for EA and RES, respectively. The amount of EA and RES were found out in the range of 1.65-9.16 mg/kg and 2.95-9.31 mg/kg in the lyophilized blueberry varieties.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Blueberry; ellagic acid; HPLC; LC-MS/MS; resveratrol